CEGAH DETEKSI DINI DALAM PENCEGAHAN PEREDARAN NARKOBA OLEH BADAN KESATUAN BANGSA DAN POLITIK DI KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Rafli Restu Prastasena; Lalu Satria Utama (Journal of Innovation Research and Knowledge, 2024)
Problem (GAP): Drug abuse is one of the serious problems faced by Indonesia, especially in the City of Palangka Raya. From the graph of drug cases from 2015-2023, it is stated that there has been a high spike in drug abuse. Purpose: To explain the efforts made by the Palangka City Government Raya handles and prevents drug trafficking from a community protection perspective. Method: This research uses a descriptive qualitative research method with an inductive approach. Data collection techniques used by researchers are interviews, observation, documentation. The theory used is the Prevent Early Detection Theory by Eva Eviany & Sutiyo 2023. Results: That Kesbangpol is still having problems in preventing drug trafficking due to the lack of public awareness of the dangers of drugs. Conclusion: The conclusion is that Kesbangpol has attempted various programs, namely continuous socialization and the establishment of the Bersinar Village to be good at preventing the circulation of drug abuse